Constructing Personal Branding as Self-Representation: A Systematic Literature Review - Muhammad Faisal; Andi Alimuddin Unde; Muhammad Farid (Psikostudia : Jurnal Psikologi, 2026)
The rapid development of digital communication technologies has fundamentally transformed how individuals construct, present, and manage their identities in contemporary society. However, most previous studies have emphasized personal branding primarily as a marketing strategy rather than as a process of identity construction and self-representation, resulting in a conceptual gap in understanding the psychological, social, and symbolic dimensions of personal branding. This study aims to analyze personal branding as a process of identity construction and self-representation in the digital context, as well as to identify conceptual patterns, thematic developments, and its professional implications. The research method employs a systematic literature review using the PRISMA approach on Scopus-indexed journal articles published between 2010 and 2026. A total of 738 articles were identified in the initial stage, and after the selection process based on inclusion and exclusion criteria, 47 articles were obtained and analyzed bibliometrically and thematically using co-occurrence analysis, publication trends, and citation impact. The findings indicate that personal branding is a multidimensional process that integrates psychological identity construction, symbolic communication, and social interaction within digital environments. Authenticity, digital visibility, and social interaction emerge as key elements in shaping credibility, professional recognition, and career opportunities. Furthermore, digital platforms function as primary spaces for identity construction, enabling individuals to actively manage their self-representation and build professional legitimacy. The implications of this study affirm that personal branding is not merely a communication strategy, but a psychological and social process that plays a crucial role in professional identity development, employability enhancement, and career mobility in the digital era, while also contributing theoretically to the integration of identity psychology, communication, and branding perspectives in understanding contemporary self-representation.Perkembangan pesat teknologi komunikasi digital telah mengubah secara fundamental cara individu membangun, menampilkan, dan mengelola identitasnya dalam masyarakat kontemporer. Namun, sebagian besar penelitian sebelumnya lebih menekankan personal branding sebagai strategi pemasaran daripada sebagai proses konstruksi identitas dan representasi diri, sehingga masih terdapat kesenjangan konseptual dalam memahami dimensi psikologis, sosial, dan simbolik dari personal branding. Penelitian ini bertujuan untuk menganalisis personal branding sebagai proses konstruksi identitas dan self-representation dalam konteks digital, serta mengidentifikasi pola konseptual, perkembangan tematik, dan implikasi profesionalnya. Metode penelitian menggunakan systematic literature review dengan pendekatan PRISMA terhadap artikel jurnal terindeks Scopus yang diterbitkan antara tahun 2010–2026. Sebanyak 738 artikel diidentifikasi pada tahap awal, dan setelah proses seleksi berdasarkan kriteria inklusi dan eksklusi, diperoleh 47 artikel yang dianalisis secara bibliometrik dan tematik menggunakan analisis co-occurrence, tren publikasi, dan dampak sitasi. Hasil penelitian menunjukkan bahwa personal branding merupakan proses multidimensional yang mengintegrasikan konstruksi identitas psikologis, komunikasi simbolik, dan interaksi sosial dalam lingkungan digital. Autentisitas, visibilitas digital, dan interaksi sosial muncul sebagai elemen kunci dalam membentuk kredibilitas, pengakuan profesional, dan peluang karier. Selain itu, platform digital berperan sebagai ruang utama konstruksi identitas yang memungkinkan individu secara aktif mengelola representasi diri dan membangun legitimasi profesional. Implikasi penelitian ini menegaskan bahwa personal branding bukan sekadar strategi komunikasi, tetapi merupakan proses psikologis dan sosial yang berperan penting dalam pengembangan identitas profesional, peningkatan employability, dan mobilitas karier di era digital, serta memberikan kontribusi teoritis bagi integrasi perspektif psikologi identitas, komunikasi, dan branding dalam memahami representasi diri kontemporer.